Insulin Therapy in Type-II Diabetes Mellitus – Is it Feasible and Acceptable? - Mundra, Aditya; Jain, Dimple; Chandrakar, Vikas Raman; Lakhani, Jitendra Dewji (Indian Journal of Pharmacy Practice)
Background: Insulin, being the mainstay of treatment for type1 and certain situations in type 2 Diabetes mellitus (DM), is still not properly utilized. Thus, this study was done to know the barriers that lead to suboptimal utilization of insulin therapy by stakeholders particularly in our group of patients who were mostly from rural background. Methods: An observational, cross-sectional study with sample size of 100 patients with Type 2 DM that were prescribed with insulin or were already on insulin was done. Patient were interviewed on basis of pre-structured socio-demographic, knowledge, attitude and practice questionnaire and accordingly counseled. Data was analyzed by percentages and student’s t-test. Results: Around 58% patients, in whom insulin was indicated, were taking insulin therapy. Limited knowledge about the disease and insulin, in addition to wrongful attitude and practices were barriers to therapy. Less than 50% patients had proper knowledge and understanding about insulin therapy. They had misconception of “habit” forming character of insulin and of hypoglycemia. Social stigma, inconvenience, life-long therapy commitment, cost, phobias were other causes for resistance to the use of insulin. Conclusion: This study concludes that by understanding patient’s attitude towards insulin therapy healthcare professionals can aim to modify their misconceptions. Difference can be made by educating patients through proper counseling by clinical pharmacist in harmony with other healthcare professionals. This will not only help in delivering proper patient-centered care but will also help in improving the way patient looks at diabetes and insulin, thus revolutionizing the diabetic world.
Keywords: Clinical Pharmacist; Type2DM; Insulin Therapy; KAP Survey; KAP Questionnaire.